2020
DOI: 10.1371/journal.pone.0230843
|View full text |Cite
|
Sign up to set email alerts
|

Reporting quality and spin in abstracts of randomized clinical trials of periodontal therapy and cardiovascular disease outcomes

Abstract: Poor reporting in randomized clinical trial (RCT) abstracts reduces quality and misinforms readers. Spin, a biased presentation of findings, could frequently mislead clinicians to accept a clinical intervention despite non-significant primary outcome. Therefore, good reporting practices and absence of spin enhances research quality. We aim to assess the reporting quality and spin in abstracts of RCTs evaluating the effect of periodontal therapy on cardiovascular (CVD) outcomes. Methods PubMed, Scopus, the Coch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 56 publications
(56 reference statements)
2
15
1
Order By: Relevance
“…For this reason, allowing authors more words in their abstracts might be a simple method to improve the reporting quality of abstracts. In addition to larger word counts, reporting of trial registration and funding were also positively correlated with high-quality reporting [71] . In the multivariate analysis of relevant factors to spin severity, we found that research from non-Asian regions might be relevant to fewer spin strategies.…”
Section: Discussionmentioning
confidence: 95%
“…For this reason, allowing authors more words in their abstracts might be a simple method to improve the reporting quality of abstracts. In addition to larger word counts, reporting of trial registration and funding were also positively correlated with high-quality reporting [71] . In the multivariate analysis of relevant factors to spin severity, we found that research from non-Asian regions might be relevant to fewer spin strategies.…”
Section: Discussionmentioning
confidence: 95%
“…We need to understand the quality of the primary literature. While a poor-quality SR/MA does not necessarily mean that the included studies are also of low quality, concerns regarding their rigor have been raised (Faggion et al 2016; Shaqman et al 2020). Examining the methodological rigor of individual studies is critical to understanding the true nature of the quality of literature in the entire domain.…”
Section: Discussionmentioning
confidence: 99%
“…Investigators, authors, editors of journals, clinicians and patients all have a desire for definitive answers, and this might encourage investigators to translate their findings into definitive statements (e.g., no effect) even when this is not supported by the statistical findings. Yet, equally problematic, editors and reviewers might insist on specific language (e.g., non-significant), sometimes against the better judgement of the authors [33] . Often this insistence on specific language originates from the desire not to be seen to be creating any spin whereby borderline statistical significance is over-interpreted [6 , 29] .…”
Section: Research In Contextmentioning
confidence: 99%